Molecular Markers in Molluscs as Biomonitoring Species - Ayad M. J. Almamoori; Jasim M. Salman (Research Aspects in Biological Science Vol. 3, 2022)
Mollusks are one of the macrobenthos groups that has been identified as a useful bioindicator. Mollusks are invertebrates with the capacity to act as bio-indicators of water pollution due to their sensitivity to contaminants in ecosystems. Bivalves are often used as indicators of environmental quality. Bivalves filter water through their gills, Biomonitors, such as living mussels, are frequently utilized. Scientists remove them from the water and test their tissue for trace metal levels. This allows them to determine how much metal is present in the water and the surrounding environment. Mussels and other marine bivalves are widely used as sentinels in "mussel watch" programs to monitor levels of toxins in the coastal marine environment because of their proclivity to bioaccumulate organic or toxic compounds. The study object is to elucidate the Role of Molecular Biomarkers identification in pollution detection and Abatement.